Factorial validity and internal consistency of a practitioners' checklist for therapists in rehabilitation. Issue 4 (9th December 2021) - Ohura, Tomoko; Tsuyama, Tsutomu; Furusawa, Mai; Iitsuka, Terufumi
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Aims: The current study aimed to assess the validity and internal consistency of a 20-item checklist to help provide rehabilitation based on effective and clear goal setting. Methods: A questionnaire survey was conducted regarding rehabilitation practices followed by physical, occupational, and speech-language therapists over the past month. The questionnaire was based on a checklist covering the following four areas, each comprising five items: goal setting based on patient and family intent and therapist perspective including long-term and short-term goals; therapist's specialized analysis and focalization of problems using the International Classification of Functioning, Disability and Health to clarify work processes and behaviors that hinder high-priority activities; proposal of plans considering the evidence and environment, which clarifies options for resolution methods (plans) and evidence; and formulation and implementation of plans including patient and family intent, which determines plan frequency and implementation period. The checklist was prepared based on medical records and previous studies by two occupational therapists who had experience in providing hospital and home-visit rehabilitation. To test the factorial validity of the 20-item checklist, confirmatory factor analysis was performed, and Cronbach's α coefficients were calculated. Results: The participants' mean age was 28 (25–75th percentile, range: 25–32) years. Of the 385 participants, 163 were home-visit rehabilitation therapists. Our model revealed a fair fit to data (χ 2 statistic = 602.0) and standardized path coefficients ranged from 0.67 to 0.95. Path coefficients were at least 0.41 for all 20 items. Cronbach's α for goal setting, problem analysis, problem solving method proposals, and formulation and implementation of specific plans were 0.896, 0.890, 0.935, and 0.925, respectively. Conclusion: Based on the assessment of therapists' practice over 1 month using the developed checklist, the factorial validity and internal consistency of these checklist items were considered acceptable. Education based on these checklist items might support goal setting and planning and improve patient outcomes.